Numerical Properties of Explicit and Semi-implicit Finite Difference Scheme for Fisher's Equation - Dadang Amir Hamzah; Bayu Robiyana (Jurnal Rekayasa Teknologi dan Sains Terapan, 2019)
This paper is devoted to analize the numerical finite difference scheme for Fisher’s equations. Fisher’s equation is a parabolic type of partial differential equations for modelling the population growth in mathematical ecology. An explicit and semi-implicit finite difference schemes are constructed with the analysis of their numerical properties such as accuracy, stability and convergency respect to energy norm. An efficient algorithm is contructed to simulate the Fisher’s equation. Some numerical tests are shown in a good agreement with the numerical properties (i.e the stability scheme)